Type I interferon rapidly restricts infectious hepatitis C virus particle genesis - Meredith, Luke W.; Farquhar, Michelle J.; Tarr, Alexander W.; McKeating, Jane A. (Wiley, 2014)
Interferon-alpha (IFNα) has been used to treat chronic hepatitis C virus (HCV) infection for over 20 years with varying efficacy, depending on the infecting viral genotype. The mechanism of action of IFNα is not fully understood, but is thought to target multiple stages of the HCV lifecycle, inhibiting viral transcription and translation leading to a degradation of viral RNA and protein expression in the infected cell. IFNα induces the expression of an array of interferon-stimulated genes within minutes of receptor engagement; however, the impact of these early responses on the viral lifecycle are unknown. We demonstrate that IFNα inhibits the genesis of infectious extracellular HCV particles within 2 hours of treating infected cells, with minimal effect on the intracellular viral burden. Importantly, this short duration of IFNα treatment of infected cells significantly reduced cell-free and cell-to-cell dissemination. The secreted viral particles showed no apparent change in protein content or density, demonstrating that IFNα inhibits particle infectivity but not secretion rates. To investigate whether particles released from IFNα-treated cells have a reduced capacity to establish infection we used HCV lentiviral pseudotypes (HCVpp) and demonstrated a defect in cell entry. Using a panel of monoclonal antibodies targeting the E2 glycoprotein, we demonstrate that IFNα alters glycoprotein conformation and receptor utilization. Conclusion: These observations show a previously unreported and rapid effect of IFNα on HCV particle infectivity that inhibits de novo infection events. Evasion of this response may be a contributing factor in whether a patient achieves early or rapid virological response, a key indicator of progression to sustained virological response or clearance of viral infection. (Hepatology 2014;60:1890–1900)